2004
DOI: 10.1080/14756360310001634910
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Inhibition by 1,3-dipropyl-8-sulfophenyl-xanthine (DPSPX), an Antagonist of Adenosine Receptors

Abstract: Xanthine oxidase (XO), an enzyme involved in purine metabolism, is a source of either oxidants (superoxide radical) or antioxidants (uric acid). Interference with XO activity can lead to oxidative stress, thus contributing to the pathogenesis of cardiovascular diseases. The adenosine receptors antagonist, 1,3-dipropyl-8-sulfophenylxanthine (DPSPX), induces hypertension and cardiovascular injury in rats. Since DPSPX is a xanthine, we aimed at evaluating DPSPX's influence on XO activity to ascertain its contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Among numerous inhibitors, Y-700 (1-(3-cyano-4-neopentyloxyphenyl)-1H-pyrazole-4-carboxylic acid) was identified as the compound with the best IC 50 (5.8 nM compared to 260 nM for allopurinol) and exhibited inhibitory activity of a mixed type. Similar to febuxostat, Y-700 exhibited more potent and longer-lasting hypouricemic activity than allo/oxypurinol [139,150]. Moreover, related results suggest that Y-700 is a useful agent for the prevention of colon tumorigenesis [151].…”
Section: Febuxostatmentioning
confidence: 90%
See 1 more Smart Citation
“…Among numerous inhibitors, Y-700 (1-(3-cyano-4-neopentyloxyphenyl)-1H-pyrazole-4-carboxylic acid) was identified as the compound with the best IC 50 (5.8 nM compared to 260 nM for allopurinol) and exhibited inhibitory activity of a mixed type. Similar to febuxostat, Y-700 exhibited more potent and longer-lasting hypouricemic activity than allo/oxypurinol [139,150]. Moreover, related results suggest that Y-700 is a useful agent for the prevention of colon tumorigenesis [151].…”
Section: Febuxostatmentioning
confidence: 90%
“…The introduction of new substituents to a natural substrate produces a better affinity towards the enzyme. Based on xanthine, new purine-like analogues were reported in some related studies such as the newly synthesized 8-(n-hexylthio) xanthine and the xanthine derivative 1,3-dipropylxanthine substituted benzenesulfonic acid, both of which showed better potency than allopurinol [139,140]. One of the best irreversible inhibitors of hypoxanthine derivatives was 8-(m-(p-fluorosulfonylbenzamido)benzylthio) hypoxanthine,…”
Section: Febuxostatmentioning
confidence: 99%
“…Three years later the xanthine derivative 1,3‐dipropylxanthine substituted benzenesulfonic acid ( 5 ), already known as an adenosine receptor antagonist, was reported by Sousa et al. to be a good XO inhibitor, with an IC 50 value in the micromolar range. In vivo studies conducted in rats showed that this compound is able to decrease both the levels of uric acid and the generation of superoxide radicals.…”
Section: Purine‐based and Purine‐like Inhibitors Of Xomentioning
confidence: 99%
“…In aw ork published in 2001 by Biagi et al [33] it was reported that the newly synthesized 8-(n-hexylthio)xanthine( 4)s howed more than six times better potencyt han allopurinol. Three years later the xanthine derivative 1,3-dipropylxanthine substituted benzenesulfonic acid (5), already knowna sa na denosine receptor antagonist, was reported by Sousa et al to be ag ood XO inhibitor, [34] with an IC 50 value in the micromolar range. In vivo studies conducted in rats showedt hat this compound is able to decrease both the levels of uric acid and the generation of superoxide radicals.…”
Section: Xanthine Analoguesmentioning
confidence: 99%